2019
DOI: 10.1245/s10434-019-07182-5
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Fracture in Primary Soft-Tissue Sarcoma of the Thigh and Groin Treated with Intensity-Modulated Radiation Therapy: Observed versus Expected Risk

Abstract: Purpose.-To compare the observed risk of femoral fracture in primary soft-tissue sarcoma (STS) of the thigh/groin treated with IMRT to expected risk calculated using the Princess Margaret Hospital (PMH) nomogram. Methods.-Expected femoral fracture risk was calculated using the PMH nomogram. Cumulative risk of fracture was estimated using Kaplan-Meier statistics. Prognostic factors were assessed with univariate and multivariate analysis using Cox's stepwise regression. Results.-Between February 2002 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Folkert et al [12] observed a significant reduction of the local failure rate (8% vs. 15%) paralleled by a reduction of side effects in a large retrospective series comparing IMRT with 3D-conformal RT. In a follow-up study, they found a clear reduction in observed fractures after IMRT compared with the anticipated rate from a validated nomogram based on 3D-conformally treated patients [13]. O'Sullivan et al [14] further showed in a phase II trial, that preoperative IMRT with sparing of anticipating skin regions of wound closure during surgery might result in less perioperative wound complications.…”
Section: Perioperative Rt In Extremity/trunk Sarcomasmentioning
confidence: 97%
“…Folkert et al [12] observed a significant reduction of the local failure rate (8% vs. 15%) paralleled by a reduction of side effects in a large retrospective series comparing IMRT with 3D-conformal RT. In a follow-up study, they found a clear reduction in observed fractures after IMRT compared with the anticipated rate from a validated nomogram based on 3D-conformally treated patients [13]. O'Sullivan et al [14] further showed in a phase II trial, that preoperative IMRT with sparing of anticipating skin regions of wound closure during surgery might result in less perioperative wound complications.…”
Section: Perioperative Rt In Extremity/trunk Sarcomasmentioning
confidence: 97%
“…Though there has never been a prospective trial randomizing patients to IMRT vs. either 3D-CRT or BT, IMRT has been associated with lower rates of wound complications compared with historical 3D-CRT results (30.5 vs. 43%, respectively) [11,30], but higher rates compared with BT (19% IMRT vs. 11% BT) [24] though neither of these results were statistically significant. IMRT has some evidence of lower rates of femoral fracture [62].…”
Section: External Beam Radiation Therapy (Ebrt)mentioning
confidence: 99%
“…An additional mid-to long-term complication that can substantially impact the quality-of-life of sarcoma survivors is a radiation-associated fracture. The most recent estimates place the risk of femur fracture at 7%, after treatment with 50-66 Gy, with a median time to fracture of 2 years [62]. Radiation treatment can alter the mechanical strength of the bone [133], making it more prone to fracture after a subclinical force or progress to a complete fracture after the development of a stress reaction.…”
Section: Musculoskeletal Injury From Sts Radiotherapymentioning
confidence: 99%
“…Furthermore, thanks to possibility of achieving better dose conformality, IMRT is expected to lower the toxicity rate of 3D-CRT. This hypothesis is currently supported by two retrospective works, showing a reduction in the observed risk of femoral fracture [27] and woundrelated morbidities [28]. Furthermore, two recently-published series have shown that volumetric arc therapy (VMAT) is an alternative promising technique [29,30] with one work showing its ability to outperform IMRT in sparing dose to normal-tissue-corridor and, subsequently, the risk of lymphedema [30].…”
Section: Discussionmentioning
confidence: 88%